An inclusion complex of cucurbit[7]uril with benzimidazolyl benzyl viologen exhibits fluorescence and photochromic properties. Issue 42 (19th October 2022) - Wang, Qin; Guo, Jun-Zhuo; Luo, Dan; Ye, Ming-Fu; Lin, Rui-Lian; Sun, Wen-Qi; Liu, Jing-Xin
Abstract : A self-assembled supramolecular inclusion complex of Q[7] with benzimidazolyl benzyl viologen exhibits interesting fluorescence emission and reversible photochromism. Abstract : In order to investigate the photochromic mechanism of photochromic materials based on supramolecular host–guest systems, we designed and synthesized a unique viologen derivative (benzimidazolyl benzyl viologen, guest 1 ·Cl3 ), which does not contain oxygen atoms. The binding interaction of guest 1 3+ with host cucurbit[7]uril (Q[7]) was investigated by various techniques. The obtained supramolecular host–guest complex 1 3+ @Q[7] exhibits interesting fluorescence emission and reversible photochromism. The ESR and XPS experimental data suggest that the photochromic process of the complex 1 3+ @Q[7] comes from the electron transfer from the carbonyl O atoms of the host Q[7] to the bipyridinium N atoms of the guest 1 3+ .